Recent large increases in freshwater fluxes from Greenland into the North Atlantic - Bamber, J.; van den Broeke, M.R.; Ettema, J.; Lenaerts, J.T.M.; Rignot, Eric (John Wiley and Sons Inc., 2012)
[1] Freshwater (FW) fluxes from river runoff and precipitation minus evaporation for the pan Arctic seas are relatively well documented and prescribed in ocean GCMs. Fluxes from Greenland on the other hand are generally ignored altogether, despite their potential impacts on ocean circulation and marine biology. Here, we present a reconstruction of the spatially distributed FW flux from Greenland for 1958–2010. We find a modest increase into the Arctic Ocean during this period. Fluxes into the Irminger Basin, however, have increased by fifty percent (6.3 ± 0.5 km3 yr−2) in less than twenty years. This greatly exceeds previous estimates. For the ice sheet as a whole the rate of increase since 1992 is 16.9 ± 1.8 km3 yr−2. The cumulative FW anomaly since 1995 is 3200 ± 358 km3, which is about a third of the magnitude of the Great Salinity Anomaly (GSA) of the 1970s. If this trend continues into the future, the anomaly will exceed that of the GSA by about 2025.
Keywords: SDG 14 - Life Below Water